The impact of ceiling height on human comfort (a comparative study on residential in Seri Iskandar, Perak) / Muhammad Hiekal Othman - Othman, Muhammad Hiekal (2014)
This study focuses on the impact of ceiling height on human comfort (A comparative study on residential building in Seri Iskandar, Perak). The residential building for case study are selected in Seri Iskandar based on different height of ceiling. Case study 1 at Persiaran Iskandar Perdana 31 and case study 2 at Pekeliling Iskandar Perdana 14 is located in Seri Iskandar, Perak. It is an education based society because of the high number of educational institutes situated in the area such as Universiti Teknologi Mara (UiTM) Kampus Seri Iskandar, Perak and Universiti Teknologi Petronas (UTP), Tronoh, Perak. At Pekeliling Iskandar Perdana 14 majority of terraces are low cost. This area provides poor facilities and maintenance services.